STRATEGI PENGEMBANGAN DESA WISATA (STUDI KASUS : DESA WISATA PONGGOK) - Damanik, Dian Hotlando; Iskandar, Deden Dinar (EP FEB UNS, 2019)
Ponggok Tourism Village is one of the tourist villages in Klaten Regency which has a variety of tourism potential. Ponggok Tourism Village needs to be further developed in order to maintain existance as a Tourism Village. Viewed from tourist visits in 2017 is began decline in tourist visits. The purpose of this study is to determine alternative management strategies that must be prioritized in order to develop Ponggok Tourism Village. This study uses the Process Hierarchy Analysis (AHP) method to analyze alternatives policy that proposed by keypersons through previous interviews. There are four alternative policies, namely: adding artificial recreational facilities, adding natural tourism packages, adding cultural tourism packages and adding souvenirs typical of Ponggok Village. The results of the AHP analysis show that the adding cultural tourism packages is main priority of the development option of Tourism Village which has the highest weight The second priority is to add natural tourism packages. The third priority is to add artificial recreational facilities, and the last priority is to add to the typical souvenirs of Ponggok Village. Keywords: process hierarchy analysis (AHP), village tourism, tourism development, development strateg